Multiobjective Optimization of Mechanical Properties on Sisal-Glass Fiber-Reinforced Hybrid Composites Using Response Surface Methodology and LINGO Analysis - S. Ragunath; A. N. Shankar; K. Meena; B. Guruprasad; S. Madhu; N. Rakesh; M. Hariprabhu; S. Balamuralitharan; Nahom Daniel (Advances in Materials Science and Engineering)
The aim of this research work was to develop the optimal mechanical properties, namely, tensile strength, flexural strength, and impact strength of sisal and glass fiber-reinforced polymer hybrid composites. The sisal, in the form of short fiber, is randomly used as reinforcements for composite materials, which is rich in cellulose, economical, and easily available as well as glass fibers have low cost and have good mechanical properties. In addition, epoxy resin and hardener were for the fabrication of composites by compression molding. The selected materials are fabricated by compression molding in various concentrations on volume basics. The combination of material compositions is obtained from the design of experiments and optimum parameters determined by the Response Surface Methodology (RSM). From the investigation of mechanical properties, the sisal is the most significant factor and verified by ANOVA techniques. The multiobjective optimal levels of factors are obtained by LINGO analysis.